2015
DOI: 10.1097/aln.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

p.L1612P, a Novel Voltage-gated Sodium Channel Nav1.7 Mutation Inducing a Cold Sensitive Paroxysmal Extreme Pain Disorder

Abstract: Background: Mutations in the SCN9A gene cause chronic pain and pain insensitivity syndromes. We aimed to study clinical, genetic, and electrophysiological features of paroxysmal extreme pain disorder (PEPD) caused by a novel SCN9A mutation. Methods: Description of a 4-generation family suffering from PEPD with clinical, genetic and electrophysiological studies including patch clamp experiments assessing response to drug and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…For example, Peddareddygari LR et al demonstrated that homozygous p.G2755T mutation in exon 15 of this gene is associated with congenital insensitivity to pain (CIP) [26, 27]. Other authors have related some mutations like p.L1612P with a Cold Sensitive Paroxysmal Extreme Pain Disorder [28]. According to these data and the role of this gene in pain and cold perception, we decided to analyzed SCN9A missense SNPs (rs6746030 (p.R1150W), rs74401238 (p.R1110Q) and rs41268673 (p.P610T)) as a potential cause of genetic susceptibility for a cold-induced neuropathy like OXLIN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peddareddygari LR et al demonstrated that homozygous p.G2755T mutation in exon 15 of this gene is associated with congenital insensitivity to pain (CIP) [26, 27]. Other authors have related some mutations like p.L1612P with a Cold Sensitive Paroxysmal Extreme Pain Disorder [28]. According to these data and the role of this gene in pain and cold perception, we decided to analyzed SCN9A missense SNPs (rs6746030 (p.R1150W), rs74401238 (p.R1110Q) and rs41268673 (p.P610T)) as a potential cause of genetic susceptibility for a cold-induced neuropathy like OXLIN.…”
Section: Discussionmentioning
confidence: 99%
“…PEPD is caused by gain‐of‐function Na V 1.7 variants that mostly result in impaired fast inactivation. So far, 10 variants in Na V 1.7 are known that cause PEPD . It is thought that the variant induces a depolarizing shift of steady‐state fast inactivation, hampering channel closure during action potential electrogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
“…So far, 10 variants in Na V 1.7 are known that cause PEPD. [206][207][208][209][210][211][212] It is thought that the variant induces a depolarizing shift of steadystate fast inactivation, hampering channel closure during action potential electrogenesis.…”
Section: Voltage-gated Sodium Channelopathies In Sfnmentioning
confidence: 99%
“…The V1309D, V1309F, and V1310F mutations are located in the S4-S5 linker region of domain III and they have been shown to cause moderate destabilization of fast inactivation (Jarecki et al, 2008). The G1618R mutation, located within the S4 segment of domain IV, impairs inactivation and retains a persistent current compared to the wild-type (WT) channel (Choi et al, 2011), while another domain IV S4 segment mutation, L1623P, significantly increases ramp current and shortens recovery time from inactivation (Suter et al, 2015). Moreover, electrophysiology study showed that M1638K mutation (within the S5 segment of domain IV) generates faster recovery from inactivation than the WT channel, producing greater currents and reducing the threshold with increased number of action potentials (Fertleman et al, 2006; Dib-Hajj et al, 2008).…”
Section: Mapping Of Disease-relevant Mutations Onto the Nav17 Structmentioning
confidence: 99%